Renaissance Stupidity (Global Journal of Human-Social Science, 2019)
The Renaissance was an expansion of the Western cognitive world beyond the limits of the medieval mind. Deism was replaced by humanism as God was replaced by man at the center of thought. Christian theology, which had so restricted intellectual development to ways to prepare people for the next life in heaven, gave way to a general appreciation of this life here and now as people self-consciously gloried in and legitimatized the world of the senses. Indulging the sin of pride, reborn man presumed to stand on his own two feet and repudiated the doctrine that he needed God's support at every turn. Reason based on knowledge gained through experience openly challenged faith as the basis for belief.
Keywords: deism; art; leonardo; michelangelo; machiavelli